Acute inhalation toxicity of cotton plant dusts. Issue 3 (August 1976) - Rylander, R; Snella, M C
Abstract : The number of free lung-cells was studied in guinea-pigs after acute exposure to extracts of various cotton dusts. A good correlation was found between the increase in number of leucocytes in the airways and the number of Gram-negative bacteria in the different dusts. Experiments using the Shwartzmann reaction and the Limulus titration test demonstrated a relationship between the content of different endotoxins in the dusts and the pulmonary reaction. A model for the acute exposure effects after exposure to cotton dust is proposed.